Pola kanker tiroid periode Juli 2013 – Juni 2016 di RSUP Prof. Dr. R. D Kandou Manado - Parura, Yolanda; Pontoh, Victor; Werung, Marselus (Universitas Sam Ratulangi, 2016)
Abstract: Thyroid cancer is a common malignant disease found in endocrine system and is increasing in incidence every year, in Indonesia found around 9 from 10 malignancy. Based on histopathological types, thyroid carcinomas are divided into papillary carcinoma, follicular carcinoma, medullary carcinoma, and anaplastic carcinomas. The most common are papillary carcinoma and then follicular carcinoma. Factors that can influence the histopathological type of thyroid carcinomas is geographical factor, which most commonly found in mountainous areas. Thyroid cancer is rare in men, most often in women with a ratio of 1: 3.Conclusion: Female gender, mountainous terrain and adulthood to older people who suffered most thyroid cancer. Keywords: thyroid cancerÂ Abstrak: Kanker tiroid penyakit keganasan tersering ditemukan pada sistim endokrin dan insidennya meningkat setiap tahun, di Indonesia menempati urutan 9 dari 10 keganasan yang sering ditemukan. Berdasarkan gambaran histopatologinya, karsinoma tiroid dibagi menjadi tipe papiler, folikuler, meduler, dan anaplastik. Kasus terbanyak adalah karsinoma tiroid papiler dan terbanyak kedua adalah karsinoma tiroid folikular. Salah satu faktor yang mempengaruhi gambaran histopatologi karsinoma tiroid adalah keadaan geografis, dimana paling banyak ditemukan pada daerah pegunungan. Kanker tiroid jarang terjadi pada laki-laki, paling sering pada perempuan dengan perbandingan 1:3. Simpulan: Jenis kelamin perempuan, daerah pegunungan dan usia dewasa sampai lanjut usia yang paling banyak menderita kanker tiroid. Kata kunci: kanker tiroid